Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization - Busmann, Nadine (Conference Papers – International Studies Association, 2007)
Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization Embracing the dominant neoliberal project, many Mexican elites have prioritized economic growth and market logics over broader social goals. The unleashing of market forces globally,and the adoption of neoliberal policies nationally have had a significant impact on local communities and national culture in Mexico. Focusing on Mexican cultural production, this paper explores the shifting terrain of political struggle in the Mexican film industry. One of the central concerns of this paper is what processes and on what authority the imagined political community in Mexico is constructed, reconstructed, and reproduced in the current era of neoliberal globalization. Historically, political contestation among political, cultural and business elites has been central to the perpetuation of the national cultural project, in this paper, it is argued that the changing political landscape in Mexico has created new conditions for contestation providing sites for previously marginalized forces to challenge the hegemony of neoliberalism.Conceptualising neoliberal globalization and its application by Mexican elites in Polanyian terms?as a double movement?the paper examines the consolidation of the Mexican film coalition as a counter-movement, driven by cultural elites, which emerged to contest the hegemony of market driven politics. In this regard the paper analyzes the ideological and material foundations of this movement. Further, it examines the coalition´s efforts to create a social base from which to reshape the state´s politico-cultural agenda to ensure the survival of an indigenous film industry, thus providing (sub)national identities with an image and voice in the face of globalizing forces. It suggests that organic intellectuals built collective political agency upon the conviction that neoliberal globalization is to be resisted insofar as it subjects the nation to transnational?and hence alien?cultural, political and economic forces. Lastly, it challenges the assumption that in challenging the hegemony of neoliberalism the film community is anti-capitalist. As the evidence will reveal the motivating factors and ideological foundations driving the efforts of the film community are much more complex. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Mexico; cultural production; elite (social sciences); globalization; international studies; neoliberalism; social goals

Searching for the Theory of Practice behind the WTO's Commodification Mandate - Göpel, Maja (Conference Papers – International Studies Association, 2007)
When trying to understand the origins of the collapse of nineteenth-century civilization, Karl Polanyi identified a Great Transformation into a "starkly utopian" Self-Regulating Market (SRM). This shift entailed 2 elements: a wide-ranging re-regulation of organization and control of production processes, and the development of economic liberalism as a body of thought that provided justification of a new set of public policies that facilitated a transformation of land (nature), labor (people), and capital (money) into "fictitious commodities." Even though these factors have not originally been produced for sale, they are now organized by purchase-logics and their value determined by market signals. Philosophy of praxis approaches point out that this process of transformation is never complete. Neither the ?discovery? of new commodities, nor the expansion of market logics are natural, but the outcome of socio-political struggles. New agreements of the World Trade Organization for example render ever more elements of social life and nature as ?trade related? and under its auspices the next great commodification wave unfolds. This paper traces which type of knowledge publicly justifies the resulting floods these policies release before comparing it with concrete negotiated outcomes and their impacts. The final discussion will circle the question to which extent ?objective? science influences policy-making - or if subjective selection of sciences supports policy-selling. ..PAT.-Unpublished Manuscript
Political Science
Keywords: World Trade Organization (WTO); commodification; ideal types; institutionalism; international trade; manufacturing processes; methodology; policy sciences; trade regulation

The Intellectual Commons vs Intellectual Property: Marxian and Polanyian Perspectives on Intellectual Capital, including Remarks on Primitive Accumulation - Jessop, Bob (Conference Papers – International Studies Association, 2007)
This paper explores the increasing significance of intellectual property rights for the appropriation of surplus value in capitalism. Building on Marx's analysis of the value form and extending it to the commodification of knowledge, it develops a Marxian critique of informational capitalism based on the basic categories of value theory; inter alia, this looks at the commodification of knowledge from the viewpoint of commodity fetishism, the enclosure of traditional knowledge, the formal subsumption of intellectual labour, the real subsumption of intellectual labour, and the role of intellectual property rights as a contradictory means to support the average rate of profit for firms specializing in immaterial production (whilst enabling them to appropriate monopoly profits). The second part of the paper inquires whether these arguments lend support to a Polanyian interpretation of knowledge as a fictitious commodity. On the basis of the arguments already deployed, plus further arguments, it is suggested that knowledge can function as a non-commodity, a quasi-commodity, a fictitious commodity, a real commodity, and as fictive capital. This has interesting implications for the concepts of primitive accumulation and accumulation through dispossession. ..PAT.-Unpublished Manuscript
Political Science
Keywords: Marxist philosophy; capitalism; commodification; intellectual property; political doctrines

Four Horsemen of the Apocalypse: Marx, Weber, Schumpeter, and Polanyi - Özel, Hüseyin (2007)
This paper is an attempt at developing an analytical framework that could be helpful to understand the unstable character of the capitalist society, by drawing upon the work of four important thinkers: Marx, Weber, Schumpeter, and Polanyi. It is argued that all four share a similar vision towards capitalism, and that they are all indispensable for the thesis that the working of capitalism undermines its own institutional structure, and thus make the reproduction of the capitalist society a contradictory process. The paper advances three theses in regard of these thinkers: first, being various representatives of the German “expressivist ” tradition, they conceive human history as displaying two antinomical tendencies at the same time; namely, human self expression through creative action vs. the loss of freedom due to increasing rationalization, alienation, and domination; second, capitalism should be seen as a decisive step towards more rationalization and therefore the loss of freedom, even if it creates the preconditions of the self-realization of the “species-being”; and third, they all believe that the very success of capitalism is the basic cause of its failure.
Economics
Keywords: MARX; Karl; 1818-1883; SCHUMPETER; Joseph Alois; 1883-1950; WEBER; Max; 1864-1920; alienation; creative destruction; double movement; iron cage